Effect of diet complexity and physical form on performance of starter pigs and on efficiency of feed processing - Pollmann, S.; Behnke, Keith C.; Allee, G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
In two trials 330 crossbred pigs averaging 12 pounds were used to evaluate the effect of starter diet complexity and physical form on average daily gain, feed efficiency, and cost of gain. In a processing efficiency trial, pellet durability, amount fines returned, and power consumption were determined. A diet with milo-soybean meal as a basis (simple) was compared with one containing 3% tallow and 5% dried whey in milo-soybean meal (complex). Each was processed into three physical forms: meal, pellet, and crumble. Adding 3% tallow and 5% whey to milo-soybean meal diet did not improve performance of the starter pigs but did increase cost of gain. In Trial I, average daily gain of pigs consuming pellets or crumbles was improved over that of meal-fed pigs (P<.05). In both trials, cost of gain was the greatest for crumble-fed pigs. Starter pig diet complexity and physical form did not affect the number of days to market or weight per day of age. In the processing efficiency trial, pellet durability and fines returned for reprocessing were adversely affected by adding of whey and tallow, but rate and power efficiency were improved by including whey and tallow. These results suggest that starter pigs will perform similarly and that cost of gain will be less for pigs on a simple diet in meal form than on a more complex diet in pellets or crumbles.
Keywords: Swine; Diet complexity; Performance; Feed processing